The Influence of Temperature on the Uniaxial Compressive Strength of Rocks - Brabec, Marek; Šimáček, Roman (Vysoké učení technické v Brně,Fakulta stavební, 2024)
This study focuses on determination of the temperature effect on uniaxial compressive strength of different rock types. For our laboratory tests, we chose local greywacke from the Kobeřice quarry which is situated 10 km south of Prostějov. For comparison, datasets representing other rock types have been gathered from the literature cited. As shown in this study, the rock type structure, composition or the processes that formed the rock can influence how the compressive strength changes across the temperature range. Results of similar analyses can be utilized during the design of underground constructions or for assessment of the fire damage on a rock-based constructions.
Keywords: Rock mechanics; uniaxial compressive strength; greywacke; temperature influence